Fed up! : winning the war against childhood obesity - Okie, Susan (Joseph Henry Press, 2005)
Once dismissed by the medical profession as a purely cosmetic problem, obesity represents an ominous health threat for our children. Obesity is now second only to smoking as a preventable cause of death. Without early intervention, overweight children often become overweight adults - and we know that at any age obesity can lead to diabetes, high cholesterol, high blood pressure, heart disease, depression, and other life-threatening conditions. Diabetes and heart disease alone cause more than 780,000 deaths each year. In fact today's kids may be the first generation in U.S. history to have a shorter life expectancy than their parents.